John McLean papers - McLean, John, 1785-1861.
Correspondence, legal briefs, financial data, docket book, printed matter, file of reports, opinions, and briefs arranged by case name, and other papers relating to McLean's service as U.S. postmaster general and U.S. Supreme Court justice. Also contains material from his service as commissioner of the U.S. General Land Office. Includes his notes on arguments made before the U.S. Supreme Court in 1830, including cases argued by John MacPherson Berrien, Francis Scott Key, David Bayard Ogden, Roger Brooke Taney, Daniel Webster, and William Wirt. Subjects include the history of Washington, D.C.; Cincinnati, Ohio, Ohio state, and national politics; Indian affairs; international relations; presidential politics; secession; slavery; and the Whig Party. Correspondents include Caleb Atwater, James Buchanan, John C. Calhoun, Salmon P. Chase, John M. Clayton, Thomas Corwin, George Mifflin Dallas, John Henry Eaton, Ninian Edwards, Edward Everett, Thomas Ewing, Duff Green, Isaac Hill, Samuel D. Ingham, Richard M. Johnson, Henry Lee, James Madison, Duncan McArthur, James Monroe, Richard Peters, William C. Rives, Richard Rush, Winfield Scott, Thomas Sergeant, William Henry Seward, Edwin McMasters Stanton, Joseph Story, Charles Sumner, Roger Brooke Taney, John Tyler, Henry Dana Ward, Daniel Webster, Thurlow Weed, and James Whitcomb.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. representative from Ohio, U.S. postmaster general, and associate justice of the U.S. Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Two items from an unknown source were transferred from Miscellaneous Manuscripts Collection in 2005.
Keywords: Atwater, Caleb, -- 1778-1867 -- Correspondence; Berrien, John MacPherson, -- 1781-1856 -- Trials, litigation, etc; Buchanan, James, -- 1791-1868 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Clayton, John M. -- 1796-1856 -- Correspondence; Corwin, Thomas, -- 1794-1865 -- Correspondence; Dallas, George Mifflin, -- 1792-1864 -- Correspondence; Eaton, John Henry, -- 1790-1856 -- Correspondence; Edwards, Ninian, -- 1775-1833 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Ewing, Thomas, -- 1789-1871 -- Correspondence; Green, Duff, -- 1791-1875 -- Correspondence; Hill, Isaac, -- 1789-1851 -- Correspondence; Ingham, Samuel D. -- 1779-1860 -- Correspondence; Johnson, Richard M. -- 1780-1850 -- Correspondence; Key, Francis Scott, -- 1779-1843 -- Trials, litigation, etc; Lee, Henry, -- 1787-1837 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; McArthur, Duncan, -- 1772-1839 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Ogden, David Bayard, -- 1775-1849 -- Trials, litigation, etc; Peters, Richard, -- 1780-1848 -- Correspondence; Rives, William C. -- 1793-1868 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; Sergeant, Thomas, -- 1782-1860 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Story, Joseph, -- 1779-1845 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Trials, litigation, etc; Tyler, John, -- 1790-1862 -- Correspondence; Ward, Henry Dana, -- 1797-1884 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Trials, litigation, etc; Weed, Thurlow, -- 1797-1882 -- Correspondence; Whitcomb, James, -- 1795-1852 -- Correspondence; Wirt, William, -- 1772-1834 -- Trials, litigation, etc; United States. -- General Land Office; United States. -- Post Office Department; United States. -- Supreme Court; Whig Party (U.S.); Constitutional law -- United States; Indians of North America -- Government relations; Law -- United States; Presidents -- United States; Secession; Slavery -- United States; Cincinnati (Ohio) -- Politics and government; Ohio -- Politics and government; United States -- Foreign relations -- 1783-1865.; United States -- Politics and government -- 19th century; Washington (D.C.) -- History; Cabinet officers; Jurists; Representatives, U.S. Congress -- Ohio